Using trust degree for agents in order to assign spots in a Smart Parking - Souza De Castro, Lucas Fernando; Vaz Alves, Gleifer; Pinz Borges, André (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2017)
The process of looking a spot could be a problem. There are computing solutions being developed to optimize this problem. One of these solutions is using multiagent systems (MAS). In this paper, a MAS is developed in order to allocate spots in a smart parking using the framework JaCaMo. This paper comprises of two types of agents: manager and drivers. The manager is responsible for administrating the parking spots which will be assigned to drivers according to a corresponding degree of trust. The trust degree is a value which shows the commitment of the driver before the manager. In order to verify the effectiveness of the MAS, several simulations were conducted in empirical scenarios. Experiments show that the degree of trust impacts in the parking spot allocation process.